1996
DOI: 10.1002/etc.5620151121
|View full text |Cite
|
Sign up to set email alerts
|

Ethoxyresorufin‐O‐deethylase induction potency of polychlorinated diphenyl ethers in H4IIE rat hepatoma cells

Abstract: Abstract-Polychlorinated diphenyl ethers (PCDEs) are structurally similar to polychlorinated biphenyls (PCBs), and some PCDE congeners have been reported to cause toxic responses similar to those caused by some of the non-ortho-substituted PCBs, which are mediated by the aryl hydrocarbon receptor (AhR). Twenty-nine PCDEs were tested for their potency as AhR agonists relative to 2,3,7,3,7, by measuring their ability to induce the cytochrome P-450 1A1-associated enzyme activity, ethoxyresorufin-O-deethylase (ERO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Therefore, enzyme induction may be due to impurities with Ah-receptor binding affinity present in technical PBDE mixtures. It was shown that PCDF impurities at concentrations < 1% could completely account for the observed EROD activity of all except one of 29 tested polychlorinated diphenyl ether (PCDE) congeners (92). This study demonstrated that in studies with halogenated DEs, it is important to control the presence of potent dibenzofuran and dibenzodioxin impurities, which even at low concentrations can account for considerable biologic activity attributed to the relatively high dosages required for DEs.…”
Section: Experimental Animalsmentioning
confidence: 82%
“…Therefore, enzyme induction may be due to impurities with Ah-receptor binding affinity present in technical PBDE mixtures. It was shown that PCDF impurities at concentrations < 1% could completely account for the observed EROD activity of all except one of 29 tested polychlorinated diphenyl ether (PCDE) congeners (92). This study demonstrated that in studies with halogenated DEs, it is important to control the presence of potent dibenzofuran and dibenzodioxin impurities, which even at low concentrations can account for considerable biologic activity attributed to the relatively high dosages required for DEs.…”
Section: Experimental Animalsmentioning
confidence: 82%
“…It cannot be ruled out that the variability observed in toxicity studies with PCDEs is due to contamination of test compounds with potent AhR agonists such as PCDDs and PCDFs [22]. For instance, we were unable to use any PCDE compounds purchased from Ultra Scientific other than PCDE congener 77 for our toxicity tests because of PCDF contamination in μg/g quantities.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, various chloro‐, nitro‐, and/or trifluoromethyl‐substituted diphenyl ethers did not induce hepatic ethoxyresorufin O ‐deethylase (EROD) activity in rainbow trout [21]. Koistinen et al [22] reported that several PCDE congeners induced EROD activity in in vitro assays with rat hepatoma (H4IIE) cells, but this activity disappeared when PCDEs were cleaned‐up by Florisil column chromatography; presumably because of chromatographic separation of PCDEs from trace amounts of potent monoxygenase‐inducing contaminants. Many of the biological responses of vertebrates to HAHs, including the induction of hepatic monoxygenases, are mediated by binding to the cytosolic aryl hydrocarbon receptor (AhR), and the strength of binding of these compounds to the AhR appears to be correlated with toxic potency [14,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that the TCDD‐like porphyrin accumulation response observed in some reports may be due to small quantities of TCDD‐like impurities in the HCB preparations, which generally elicit their responses at micromolar concentrations [43,44]. The importance of verifying purity was recently exemplified by the observation that the ability of polychlorinated diphenyl ether preparations to induce EROD activity in H4IIE rat hepatoma cells was due to low concentrations of PCDF impurities, which were well below 1% [45]. Aryl hydrocarbon‐active impurities, such as PCDDs, PCDFs, and non‐ ortho ‐PCBs were not detected by GC‐MS and GC‐ECD in the HCB preparation used in the present study.…”
Section: Discussionmentioning
confidence: 99%